Multiple Brain Abscesses due to Streptococcus anginosus: Prediction of Mortality by an Imaging Severity Index Score - K. O. Kragha (Case Reports in Radiology)
An elderly patient with altered mental status, brain abscesses, ventriculitis, and empyemas died of septic shock and brain abscesses secondary to Streptococcus anginosus despite aggressive treatment. An imaging severity index score with a better prognostic value than the Glasgow coma scale predicted mortality in this patient.